2011
DOI: 10.1117/1.3662458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross-linking with riboflavin and ultraviolet A on the chemical bonds and ultrastructure of human sclera

Abstract: Abstract. This study examined the effect of the cross-linking with riboflavin-ultraviolet A (UVA) irradiation on the chemical bonds and ultrastructural changes of human sclera tissues using Raman spectroscopy and atomic force microscopy (AFM). Raman spectroscopy of the normal and cross-linked human sclera tissue revealed different types of the riboflavin-UVA and collagen interactions, which could be identified from their unique peaks, intensity, and shape. Raman spectroscopy can prove to be a powerful tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 34 publications
8
20
2
2
Order By: Relevance
“…Micro-Raman analysis revealed characteristic accentuation and shift in both amide-I and -III bands with crosslinking, which is consistent with previous reports of collagen type-I crosslinked with riboflavin (Jung et al, 2011) or glutaraldehyde (Jastrzebska et al, 2003). In addition, the amide-I band was associated with the stretching-vibration of the peptide carbonyl groups, whereas the amide-III band resulted from the NH in-plane deformation coupled to CN-stretching.…”
Section: Discussionsupporting
confidence: 88%
“…Micro-Raman analysis revealed characteristic accentuation and shift in both amide-I and -III bands with crosslinking, which is consistent with previous reports of collagen type-I crosslinked with riboflavin (Jung et al, 2011) or glutaraldehyde (Jastrzebska et al, 2003). In addition, the amide-I band was associated with the stretching-vibration of the peptide carbonyl groups, whereas the amide-III band resulted from the NH in-plane deformation coupled to CN-stretching.…”
Section: Discussionsupporting
confidence: 88%
“…The UV dose‐dependent stiffness controllability was further demonstrated by the FTIR spectroscopic analysis given that the chemical changes in the compressed collagen construct can alter the IR absorption in the FTIR spectroscopic analysis. Previous studies showed that an increase in peak values of the amide bands is associated with the riboflavin‐mediated crosslinking and consequent stiffness increase (Chan, Choy, & Lai, ; Jung et al, ). The gradual changes of the IR absorptions, at amide A, I, II, and III bands, in this study indicated the UV dose‐dependent covalent bonds formation, which was similar to the trend observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, physical methods, specifically ultraviolet radiation, have been tried in dentistry and in ophthalmology . Ultraviolet (UVA)‐activated riboflavin has been shown to increase bond strength, stabilize the adhesive interface, and inhibit dentin MMPs .…”
Section: Methods To Increase the Durability Of Dentin Bondsmentioning
confidence: 99%